CD4+CD25+FOXP3+ regulatory T cells suppress anti-tumor immune responses in patients with colorectal cancer. - Sarah L Clarke; Gareth J Betts; Andrea Plant; Kate L Wright; Tariq M El-Shanawany; Richard Harrop; Jared Torkington; Brian I Rees; Geraint T Williams; Awen M Gallimore; Andrew J Godkin (PLoS ONE)
Background A wealth of evidence obtained using mouse models indicates that CD4(+)CD25(+)FOXP3(+) regulatory T cells (Treg) maintain peripheral tolerance to self-antigens and also inhibit anti-tumor immune responses. To date there is limited information about CD4(+) T cell responses in patients with colorectal cancer (CRC). We set out to measure T cell responses to a tumor-associated antigen and examine whether Treg impinge on those anti-tumor immune responses in CRC patients. Methodology and principal findings Treg were identified and characterized as CD4(+)CD25(+)FOXP3(+) using flow cytometry. An increased frequency of Treg was demonstrated in both peripheral blood and mesenteric lymph nodes of patients with colorectal cancer (CRC) compared with either healthy controls or patients with inflammatory bowel disease (IBD). Depletion of Treg from peripheral blood mononuclear cells (PBMC) of CRC patients unmasked CD4(+) T cell responses, as observed by IFNgamma release, to the tumor associated antigen 5T4, whereas no effect was observed in a healthy age-matched control group. Conclusions/significance Collectively, these data demonstrate that Treg capable of inhibiting tumor associated antigen-specific immune responses are enriched in patients with CRC. These results support a rationale for manipulating Treg to enhance cancer immunotherapy.